Early Modern German Shakespeare: Titus Andronicus and The Taming of the Shrew Tito Andronico and Kunst über alle Künste, ein bös Weib gut zu machen in Translation - Shakespeare, William (Bloomsbury Academic, 2022)
This open access book provides translations of early German versions of Titus Andronicus and The Taming of the Shrew. The introductory material situates these plays in their German context and discusses the insights they offer into the original English texts. English itinerant players toured in northern Continental Europe from the 1580s. Their repertories initially consisted of plays from the London theatre, but over time the players learnt German, and German players joined the companies, meaning the dramatic texts were adapted and translated into German. There are four plays that can legitimately be considered as versions of Shakespeare's plays. The present volume (volume 2) offers fully-edited translations of two of them: Tito Andronico (Titus Andronicus) and Kunst über alle Künste, ein bös Weib gut zu machen / An Art beyond All Arts, to Make a Bad Wife Good (The Taming of the Shrew). For the other two plays, Der Bestrafte Brudermord / Fratricide Punished (Hamlet) and Romio und Julieta (Romeo and Juliet), see volume 1. These plays are of great interest not only to all Shakespeareans, but also to scholars who are concerned with the broader issues of translation, performance and textual transmission over time. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Swiss National Science Foundation.